The Effect of Coconut Water on the Growth of Aloe vera Plants as a Source of Biology Learning - Sandi Laili Magfiroh; Imas Cintamulya (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Contextual biology learning requires locally based learning resources that are easy to apply in research activities. One local resource is coconut water, which contains nutrients and natural growth hormones to support plant growth. This study aims to determine the effect of coconut water on the growth of Aloe vera plants and to identify the optimal concentrations of coconut water for different growth parameters, as a locally based biology learning resource. The method used was a completely randomized experimental design with five coconut water concentration treatments (20%, 40%, 60%, 80%, and 100%) and five replicates per treatment. The growth parameters observed included the number of leaves, leaf height, and root length over a four-week period. The data were analysed using ANOVA and Duncan's post hoc test at the 5% significance level. The results showed that coconut water significantly affected Aloe vera growth (p < 0,05). The 80% concentration produced the highest number of leaves (5,35 leaves), the 100% concentration produced the highest leaf height (11.50 cm), and the 60% concentration produced the greatest root length (3.95 cm). These findings indicate that different growth parameters responded optimally to different coconut water concentrations. These findings suggest that coconut water can serve as an affordable, locally available resource for biology education, enabling students to conduct experimental investigations into plant growth while developing skills in observation, measurement, data analysis, and scientific reasoning.